(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Langston Hughes (1902–1967) stands as one of the most influential figures of the Harlem Renaissance, a cultural movement that celebrated African American art, literature, and identity in the 1920s. Born in Joplin, Missouri, Hughes drew inspiration from his experiences growing up in the racially segregated Midwest, as well as the rich traditions of Black culture, particularly jazz, blues, and oral storytelling. His works, including iconic poems like The Negro Speaks of Rivers and I, Too, gave voice to the struggles, dreams, and resilience of African Americans. Hughes’s literary style was groundbreaking, characterized by its embrace of vernacular speech, rhythmic patterns inspired by jazz, and vivid portrayals of everyday Black life. Unlike contemporaries who sought to align African American art with European traditions, Hughes championed the authenticity of Black cultural expression. His focus on working-class experiences and his rejection of stereotypes reshaped American literature, offering a powerful counter-narrative to mainstream depictions of African Americans.